Additive Engineering for Stable and Efficient Dion–Jacobson Phase Perovskite Solar Cells - Liu, Min; Pauporté, Thierry (Nano-Micro Letters, 2023)
Because of their better chemical stability and fascinating anisotropic characteristics, Dion–Jacobson (DJ)-layered halide perovskites, which owe crystallographic two-dimensional structures, have fascinated growing attention for solar devices. DJ-layered halide perovskites have special structural and photoelectronic features that allow the van der Waals gap to be eliminated or reduced. DJ-layered halide perovskites have improved photophysical characteristics, resulting in improved photovoltaic performance. Nevertheless, owing to the nature of the solution procedure and the fast crystal development of DJ perovskite thin layers, the precursor compositions and processing circumstances can cause a variety of defects to occur. The application of additives can impact DJ perovskite crystallization and film generation, trap passivation in the bulk and/or at the surface, interface structure, and energetic tuning. This study discusses recent developments in additive engineering for DJ multilayer halide perovskite film production. Several additive-assisted bulk and interface optimization methodologies are summarized. Lastly, an overview of research developments in additive engineering in the production of DJ-layered halide perovskite solar cells is offered. Highlights: 1 Soluble compounds are added to the Dion–Jacobson (DJ) perovskite precursor solutions. 2 Current studies and development trends of additive compounds in DJ-phase perovskite solar cells are reviewed. 3 The innate functions of additive compounds in DJ-phase perovskite solar cells are developed. 4 An insightful perspective is outlined for future research in additive compounds for DJ-phase perovskite solar cells.